Differentiated training model for marathon runners on building tempo and speed endurance based on the types of energy metabolism - Bakayev, V.; Bolotin, A. (SportMont, 2020)
This article discusses the issues of improving the quality of the training process for marathon runners in competition preparation by utilizing the application of a differentiated training model based on the types of energy metabolism for the development of tempo and speed endurance. The studies conducted have shown that marathon runners of different energy metabolism types adapt differently to competitive loads, as well as to speed and tempo development. The process of adaptation of their functional systems (which define tempo and speed endurance) occurs mainly due to the differentiation of the tools and methods used correspondingly to the type of energy metabolism. It allows not only for the more effective expansion of the cardiorespiratory system capabilities but also for bringing athletes to a higher level of tempo and speed endurance development. As a result of the study, it was revealed that for aerobic athletes, tempo endurance should be developed by using standard continuous training, while speed endurance should be developed through repeated training. Tempo endurance in anaerobic marathon runners should be developed by using interval training, while speed endurance should be developed through non-maximal effort training with a normalized number of distance segments. Tempo endurance in marathon runners of the mixed type of energy metabolism should be developed by using the variable training method, while speed endurance should be developed through a combination of non-maximal effort and repeated training with a fixed number of distance segments.